Eye Blink to Speech Conversion for Paralyzed (MND) Patients Using ML Based Algorithm - Ananda Babu, J; Keerthi, K S; Tejonidhi, R M; Sangeetha, S; Kumar, R. (2022 IEEE International Conference on Data Science and Information System (ICDSIS), 2022)
People suffering from Motor Neurone Disease (MND) will not be able to move any body part except eye blink and eye movement. They find it difficult to communicate. This project helps them to overcome the situation by making use of the eye blink. The camera in front of the person captures the eye blink of the patient, analyses the blink pattern and converts it into speech. It uses the Haar Cascade Classifiers for Face and Eye detection in real time video with OpenCV. The system is designed considering the limitations of the existing system, as they employ extra hardware and are expensive.